HUKUM JAMINAN FIDUSIA DI INDONESIA - Imron A Imron A; Maiyusmadi Maiyusmadi; Wydianani Wydianani (Jurnal Program Pascasarjana Ilmu Hukum Universitas Islam As-Syafi'iyah, 2016)
Fiduciary guarantee is stipulated in Law No. 42 1999 was a transfer of ownershipof an object on the basis of trust, so that objects that the transferred ownershiprights remain in the control of the owner of the object. Thus due to the mastery ofthe physical object is at Fiduciary Giver, then the time will be right eksekutorial byFiduciary receiver, sometimes the object of Fiducia Security has been damaged orlost or changed hands or sold; The value of fiduciary does not fit anymore becauseit is damaged, not maintained debtor properly, causing losses to the bank; Specialobject of collateral in the form of stock / inventory, equipment (inventory),furniture, machines have been transferred by the debtor without the knowledge ofthe bank; eksekutorial that directly can be done in the execution of fiduciary, inpractice by the Management Office officials State Receivables and Auction KP2LNmust be sought from a court warrant.